A bias-corrected histogram estimator for line transect sampling. Issue 15 (3rd August 2018) - Eidous, Omar; Al-Eibood, Fahid
ABSTRACT: The classical histogram method has already been applied in line transect sampling to estimate the parameter f (0), which in turns is used to estimate the population abundance D or the population size N . It is well know that the bias convergence rate for histogram estimator of f (0) is o ( h 2 ) as h → 0, under the shoulder condition assumption. If the shoulder condition is not true, then the bias convergence rate is only o ( h ). This paper proposed two new estimators for f (0), which can be considered as modifications of the classical histogram estimator. The first estimator is derived when the shoulder condition is assumed to be valid and it reduces the bias convergence rate from o ( h 2 ) to o ( h 3 ). The other one is constructed without using the shoulder condition assumption and it reduces the bias convergence rate from o ( h ) to o ( h 2 ). The asymptotic properties of the proposed estimators are derived and formulas for bin width are also given. The finite properties based on a real data set and an extensive simulation study demonstrated the potential practical use of the proposed estimators.